Electromechanical coupling coefficient of 1-3 connectivity barium titanate-portland cement composites - Rianyoi R. (2014)
This paper reports electromechanical properties of the newly developed 1-3 connectivity lead-free piezoelectric ceramic-Portland cement composites for smart structure applications. The composites were fabricated from barium titanate and Portland cement by the dice-and-fill method. The influences of barium titanate (BT) ceramic volume fractions from 30% to 70% on the electromechanical coupling coefficient of composite were investigated. The results indicate that the thickness electromechanical coupling coefficient (Kt) of the composite is influenced by the BT volume content. It was found that the thickness electromechanical coupling coefficient (Kt) could reach up to 21.52% when the composite with BT ceramic volume content was increased to 70%. © 2013 Copyright Taylor and Francis Group, LLC.